Cross-cultural adaptation and validation of the Chinese version of the Spine Oncology Study Group Outcomes Questionnaire - Zhai, Shuheng; Xu, Nanfang; Liu, Shanshan; Liu, Zhongjun; Liu, Xiaoguang; Wei, Feng (Frontiers in Oncology, 2022)
Background context Patients with spinal metastases always have a poor health-related quality of life (HRQoL) and disease- and treatment-related adverse outcomes. The Spine Oncology Study Group Outcomes Questionnaire (SOSGOQ) has been verified and validated in English for patients with spinal metastases but not in Chinese. Purpose This paper aimed to complete the cross-cultural adaptation of the Chinese version of the SOSGOQ, to verify its reliability and validity, and to report on the HRQoL of Chinese patients with spinal metastases. Study design/setting This is a single-center, prospective, observational cross-sectional study. Patient sample Seventy-six patients were enrolled in this study. Outcome measures The SOSGOQ is made up of five HRQoL domains (physical function, neurological function, pain, mental health, social function) and post-therapy questions. The EQ-5D 3L questionnaire covers five items in mobility, self-care, usual activities, pain discomfort, and anxiety-depression, each with three answer options. The SF-36 comprises 36 items divided into eight domains. Methods A single-center, prospective, observational cross-sectional study involving patients with spinal metastases who underwent surgery was conducted. HRQoL was evaluated using the Chinese version of the SOSGOQ, the Medical Outcomes Study Questionnaire Short Form 36 Health Survey (SF-36), and the EuroQol 5-Dimension questionnaire (EQ-5D). Demographic, tumor, symptom, and treatment data, as well as Eastern Cooperative Oncology Group (ECOG) information, were collected. Internal consistency reliability, convergent validity, concurrent validity, and clinical validity were used to evaluate reliability. A Spearman’s correlation analysis was used to analyze the relationship between variables. Results This study enrolled 76 patients, with a mean age of 55.8 years. The kidney was the most common primary tumor site, and the thoracic spine was the most affected. The internal consistency of the overall SOSQOQ (0.907) was higher than the EQ-5D (0.819), and all items of the SOSQOQ had a high convergent validity (>0.40). The SOSGOQ was significantly correlated with the EQ-5D in respective domains (p < 0.001) and overall score (p < 0.001), whereas the SF-36 was related to the overall SOSGOQ score and most domains. Total SOSGOG was significantly sensitive to changes in ECOG (p = 0.017), prior surgery (p = 0.001), and tumor type (p = 0.026). Conclusions The SOSGOQ is a reliable and effective tool for evaluating HRQoL in patients with spinal metastases, with high sensitivity and specificity. Surgical treatment can significantly improve patients’ HRQoL.